Sharia Bank Deposits and Financing: Does Economic Turbulence Matter? - Lutfi, Lutfi (Journal of Economics, Business, and Accountancy Ventura, 2023)
The decline in national economic performance as a result of COVID-19 can cause a reduction in company and community income, which will reduce the availability of third-party funds and financing channeled by Sharia banks. This research aims to examine the determinants of third-party deposits and Sharia bank financing in Indonesia using a sample of ten Sharia banks from 2017-2022 that did not carry out mergers or acquisitions. Testing was also carried out on each type of deposit and financing contract because of the potential for different behavior between types of contracts. Data were analyzed using panel data techniques, where the selected model had a fixed effect. The test results prove that there is a positive reciprocal influence between third-party deposits and Sharia bank financing. Economic turbulence has a significant negative impact on deposits, but it is not significant on financing. This turbulence significantly only reduced profit-sharing deposits but not wadiah deposits. Likewise, this economic condition only has a negative impact on financing with receivables contracts but not on profit-sharing financing. This finding implies the importance of Sharia banks in maintaining adequate availability of third-party funds to support financing growth. The Government and Bank Indonesia are important to maintain economic stability. Furthermore, the Financial Services Authority needs to increase monitoring of banks with low capital because of the potential for moral hazard.